Structural analysis of cannabinoids against EGFR-TK leads a novel target against EGFR-driven cell lines - Thomanai Lamtha; Lueacha Tabtimmai; Napat Songtawee; Natthasit Tansakul; Kiattawee Choowongkomon (Elsevier, 2022)
Epidermal growth factor receptor (EGFR) is a member of the ErbB family of proteins and are involved in downstream signal transduction, plays prominent roles in cell growth regulation, proliferation, and the differentiation of many cell types. They are correlated with the stage and severity of cancer. Therefore, EGFRs are targeted proteins for the design of new drugs to treat cancers that overexpress these proteins. Currently, several bioactive natural extracts are being studied for therapeutic purposes. Cannabis has been reported in many studies to have beneficial medicinal effects, such as anti-inflammatory, analgesic, antibacterial, and anti-inflammatory effects, and antitumor activity. However, it is unclear whether cannabinoids reduce intracellular signaling by inhibiting tyrosine kinase phosphorylation. In this study, cannabinoids (CBD, CBG, and CBN) were simulated for binding to the EGFR-intracellular domain to evaluate the binding energy and binding mode based on molecular docking simulation. The results showed that the binding site was almost always located at the kinase active site. In addition, the compounds were tested for binding affinity and demonstrated their ability to inhibit kinase enzymes. Furthermore, the compounds potently inhibited cellular survival and apoptosis induction in either of the EGFR-overexpressing cell lines.